2001
DOI: 10.1029/2000gl012383
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of electron phase‐space holes in 3D

Abstract: Abstract.Electron phase-space holes are regions of depleted electron density commonly generated during the nonlinear stage of the two-stream instability. Recently, bipolar electric field structures a signature of electron holes have been identified in the acceleration region of the auroral ionosphere. This paper compares the evolution of electron holes in 2-D and 3-D using massively-parallel PIC simulations. In 2-D, the holes decay after hundreds of plasma periods while emitting electrostatic whistler waves. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 21 publications
(27 reference statements)
8
95
1
Order By: Relevance
“…It is interesting to also note that Singh et al (2001) observed radiation of small amplitude waves when phase space vortices underwent rapid changes (in their case electron holes radiating plasma waves). Related observations were made by Newman et al (2001) and Oppenheim et al (2001).…”
Section: Numerical Resultsmentioning
confidence: 70%
“…It is interesting to also note that Singh et al (2001) observed radiation of small amplitude waves when phase space vortices underwent rapid changes (in their case electron holes radiating plasma waves). Related observations were made by Newman et al (2001) and Oppenheim et al (2001).…”
Section: Numerical Resultsmentioning
confidence: 70%
“…Berk et al, 1970;Schamel, 1979;Dupree, 1982;Omura et al, 1994;Krasovsky et al, 1997;Goldman et al, 1999;Krasovsky et al, 1999a;Franz et al, 2000;Oppenheim et al, 2001). Although the solitary waves recorded by Geotail look like almost plane perturbations or one-dimensional solitons, the solitary potential structures observed by the FAST and POLAR satellites resemble perturbations of an ellipsoidal, sometimes almost spherical shape (Ergun et al, 1998;Franz et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…To be an important radiation source via the electron-cyclotron maser mechanism, EHs should produce steep positive velocity space gradients on the electron distribution function both in the perpendicular and parallel directions (Treumann et al, 2011). It is important to mention that, thus far, perpendicular velocity space data are unfortunately not represented in numerical magnetized simulations (Oppenheim et al, 2001).…”
Section: Electron Holes As Radiating Antennasmentioning
confidence: 99%